Molecular classification of Crohn's disease reveals two clinically relevant subtypes. Issue 1 (14th October 2016) - Weiser, Matthew; Simon, Jeremy M; Kochar, Bharati; Tovar, Adelaide; Israel, Jennifer W; Robinson, Adam; Gipson, Gregory R; Schaner, Matthew S; Herfarth, Hans H; Sartor, R Balfour; McGovern, Dermot P B; Rahbar, Reza; et al.
Abstract : Objective: The clinical presentation and course of Crohn's disease (CD) is highly variable. We sought to better understand the cellular and molecular mechanisms that guide this heterogeneity, and characterise the cellular processes associated with disease phenotypes. Design: We examined both gene expression and gene regulation (chromatin accessibility) in non-inflamed colon tissue from a cohort of adult patients with CD and control patients. To support the generality of our findings, we analysed previously published expression data from a large cohort of treatment-naïve paediatric CD and control ileum. Results: We found that adult patients with CD clearly segregated into two classes based on colon tissue gene expression—one that largely resembled the normal colon and one where certain genes showed expression patterns normally specific to the ileum. These classes were supported by changes in gene regulatory profiles observed at the level of chromatin accessibility, reflective of a fundamental shift in underlying molecular phenotypes. Furthermore, gene expression from the ilea of a treatment-naïve cohort of paediatric patients with CD could be similarly subdivided into colon-like and ileum-like classes. Finally, expression patterns within these CD subclasses highlight large-scale differences in the immune response and aspects of cellular metabolism, and were associated with multiple clinical phenotypes describing disease behaviour, including rectal disease and need for colectomy. Conclusions: Our results strongly suggest that these molecular signatures define two clinically relevant forms of CD irrespective of tissue sampling location, patient age or treatment status.